تحليل اقتصادي للعوامل المؤثرة على حجم ونمط وتكلفة الواردات في السودان في الفترة (1980- 2016م) - آدم حامد, حامد معلى (Gezira Journal of Economic and Social Sciences; مجلد 10 عدد 2 (2019), 2020)
هدف البحث إلى تقدير العوامل المؤثرة على حجم ونمط وتكلفة الواردات في السودان. تمثلت فرضية البحث في أن حجم ونمط وتكلفة الواردات في السودان يعتمد في تفسيره على الناتج القومي الإجمالي وضريبة الواردات وسعر الصرف ودرجة الانفتاح الخارجي وعلى هذا الأساس تم استخدام المنهج الوصفي في الجانب النظري، أما في الجانب التطبيقي فقد تم استخدام أسلوب الاقتصاد القياسي وتوظيف تقنيات تحليل السكون والتكامل المشترك وطريقة المربعات الصغرى العادية في تقدير النموذج لمعرفة أثر العوامل التي تحدد حجم ونمط وتكلفة الواردات في السودان عبر برنامج Eviews10.  توّصل البحث إلى أن جميع متغيرات البحث غير مستقرة في مستوياتها وهذا يتناسب مع طبيعة المتغيرات الاقتصادية . وثبات معنوية جميع المتغيرات التفسيرية وهذا يؤكد أن سعر الصرف والناتج القومي الإجمالي وضريبة الواردات ودرجة الانفتاح الخارجي تؤثر على حجم ونمط وتكلفة الواردات في السودان. من توصيات البحث انتهاج سياسات اقتصادية تحدث آثار ايجابية في حجم ونمط وتكلفة الواردات من جهة وضبط سعر الصرف وإزالة آثار التضخم لتحقيق الاستقرار الاقتصادي من جهة أخرى. The aim of the research is to estimate the factors affecting the size, pattern and cost of imports in Sudan. The research hypothesis is that the size, pattern, and cost of imports in Sudan depend in its interpretation on the Gross National Product(GDP), import tax, the exchange rate and the degree of external openness. On this basis, the descriptive approach was used in the theoretical side, and on the practical side the econometric method was used and the techniques of static analysis were employed and the joint complementarity and the ordinary least squares method in estimating the model were used to know the effect of factors that determine the size, pattern and cost of imports in Sudan through Eviews10 program. The research came out with that all research variables are not stable in their levels, and this is consistent with the nature of the economic variables. The significance of all the explanatory variables has been proven, and it confirms that the exchange rate, (GNP), import tax and the degree of external openness  affects the size, pattern and cost of imports in Sudan. Among the recommendations of the research are the adoption of economic policies that have positive effects on the volume, pattern and cost of imports on one hand, control the exchange rate and remove the effects of inflation to achieve economic stability on the other.